Immunomagnetic separation and solid-phase detection of Bordetella pertussis. - Stark, M (1996)
In the present study, novel solid-phase methods were used for both sample preparation and PCR detection of Bordetella pertussis. The sample preparation was performed by immunomagnetic separation with paramagnetic beads coated with polyclonal antibodies directed toward the surface antigens of the bacteria. The precoated immunobeads were directly used on nasopharyngeal aspirates to capture the bacteria on the solid support and were subsequently transferred to the PCR tube with no further manipulations. The region encompassing the pertussis toxin promoter was analyzed to allow direct discrimination between the three major Bordetella species (B. pertussis, B. parapertussis, and B. bronchiseptica). The resulting amplicons were captured on a second magnetic solid phase, allowing detection and restriction analysis of the target sequence. A colorimetric detection system based on a DNA binding fusion protein enabled the use of standardized enzyme-linked immunosorbent format tests both for the detection of Bordetella spp. and for species evaluation. When the optimized system was evaluated on 55 clinical aspirate samples, 21 of 22 (95%) culture-positive samples were positive by the system that we developed. In addition, two samples were positive by the PCR-based assay, while the culture assay was negative. The implications of these results are discussed.